(untitled) (Journal of Economic Research & Business Administration, 2018)
Over the past decades, the world is rapidly moving towards a new type of economy, where digital technologies are becoming the main tool for its formation. In modern conditions, information technologies and digital transformation are the main factor of technological change and the condition for ensuring competitiveness both at the level of individual enterprises and at the level of countries and supranational associations, leading to the restructuring of all economic and production processes, radical improvements in productivity, quality improvement and cost reduction goods and services. Modern world governmental institutions and business environment strive for comprehensive and complex development. Thus, it becoming more evident that activities of our society require implementing new texnologies such as digital economy. Logistics, being a complex and multistage process hugely intervening into modern market relationships, requires constant evolution so that it could bring more efficiency into business and economic processes. Implementation of the digital technology into logistics may give an impulse to achieve goals set by the government. The article covers such topics, as general steps of logistics development, application of digital texnology, issuses associated with implementation of digital technology into logistics processes.